Preparation method of coal gangue mixed solid waste mineralization column
Through the mixed preparation of coal gangue, fly ash, gypsum and alkaline substances, mineralized columns are formed, which solves the coal resource loss and environmental pollution caused by the coal column support method, and achieves efficient and economical goaf treatment and waste resource utilization.
Patent Information
- Application Number
- CN202510026238.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-11
AI Technical Summary
The coal pillar support method leads to coal resource losses and environmental pollution during coal mining, and has high production costs, which affects mining efficiency and safety.
Mineralized columns are prepared by mixing coal gangue, fly ash, gypsum and alkaline substances (such as calcium carbide slag). Prefabricated parts are formed by mixing, wheel milling, injection molding, pressing and autoclaving to replace coal columns and support the overlying rock layer.
It reduces coal resource losses, reduces environmental pollution, improves coal mining rate and economic benefits, and realizes resource utilization of waste.
Abstract
Description
Technical Field
[0001] The invention relates to a technology for comprehensively utilizing waste slag to burn building materials, and in particular to a method for preparing a coal gangue mixed solid waste mineralized column. Background Art
[0002] In the vast field of coal mining, effective treatment of goaf is a key link to ensure mine safety, maintain surface stability, and promote sustainable use of resources. The coal pillar support method, as a traditional technology with a long history in this field, is based on the basic principle of using the physical strength of the coal pillar to bear the weight of the overlying rock strata, thereby preventing large-scale collapse of the goaf and providing the necessary safety barrier for mine operations.
[0003] Specifically, the coal pillar support method intentionally leaves coal pillars of a certain width and spacing during the mining process through precise calculation and design. These coal pillars are like natural "pillars" that support the overlying rock structure, effectively limiting the range and speed of rock movement, and thus controlling the degree of surface subsidence. In mining areas with relatively stable geological conditions and relatively simple rock structures, this method can play a good role, not only ensuring the safe production of mines, but also reducing environmental problems caused by surface subsidence and social costs such as relocation of residents.
[0004] However, with the continuous advancement of coal mining technology and the continuous increase in mining depth, the limitations of the coal pillar support method have become increasingly prominent. As a traditional method for dealing with goaf in coal mining, the core idea of the coal pillar support method is to support the overlying rock strata by leaving a coal pillar of a specific width in the goaf to prevent it from collapsing due to loss of support. This method has a certain application effect under specific geological conditions and can effectively control surface subsidence and ensure mine safety. However, its limitations are also obvious: first, the leaving of coal pillars leads to direct loss of coal resources and reduces mining efficiency; second, frequent excavation operations increase production costs, and frequent relocation of working faces affects production continuity; third, the long-term existence of coal pillars constitutes an obstacle to the mining of the lower coal seams, increasing the difficulty and risk of subsequent mining. Therefore, exploring more efficient and economic goaf treatment technologies and reducing coal resource losses have become urgent issues to be solved in the coal industry. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing a coal gangue mixed solid waste mineralized column, which can reduce the loss of coal resources and reduce pollution to the environment.
[0006] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a coal gangue mixed solid waste mineralized column, which specifically comprises the following steps: The coal gangue is crushed and mixed with fly ash, gypsum and water to form a slurry, which is then stirred and rolled; alkaline substances are added to dissolve it, and then a prefabricated product is finally formed after injection molding, pressing and curing, namely, a coal gangue mixed solid waste mineralized column; The mass ratio of the coal gangue, fly ash, gypsum and alkaline substance is 25:50:15:10.
[0007] Preferably, the alkaline substance is carbide slag.
[0008] Preferably, the mass ratio of the total mass of the coal gangue, fly ash and gypsum to water is (3-5):1.
[0009] Preferably, the curing process is an autoclave curing process.
[0010] Preferably, the autoclave curing process is curing at 180-190° C. and 1-2 MPa for 8-12 hours.
[0011] Preferably, the strength of the preform is not less than 38Mpa.
[0012] Preferably, the strength of the preform is 42Mpa.
[0013] Preferably, the particle size of the coal gangue after crushing is 2~10mm.
[0014] Preferably, the particle size of the coal gangue after crushing is 2 mm.
[0015] Preferably, the stirring rate is 300-400 rpm.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, fly ash and gypsum have mineralization and hydration activities, participate in mineralization reaction and hydration reaction, produce cementitious structure, and use them as active materials of cementitious components. Coal gangue does not participate in the reaction during the curing process, and plays a structural support role as aggregate; carbide slag ensures the absorption of more CO2 gas on the one hand, and releases more heat on the other hand, ensuring the autoclave curing effect, effectively delaying the solidification of the slurry, and ensuring that more gas enters the interior to react with free calcium oxide to form strength. The present invention adopts an environmentally friendly concrete formula to replace coal pillars, increase the mining rate of coal, improve economic benefits, comprehensively utilize various wastes in coal mine production and power plant power generation, and reduce pollution to the environment. DETAILED DESCRIPTION
[0017] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0018] It should be noted that when an element is referred to as being "disposed on" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and are not intended to be the only embodiment.
[0019] Coal gangue is solid waste discharged during the coal mining and coal washing process. It is a kind of black-gray rock with low carbon content and harder than coal that accompanies the coal seam during the coal formation process. It includes excavation gangue during tunnel excavation, gangue mined from the roof, floor and interlayer during mining, and washed gangue picked out during coal washing. Its main components are Al2O3 and SiO2. The abandonment of coal gangue will occupy a large area of land, and the escape or leaching of sulfides in it will pollute the atmosphere, farmland and water bodies. Gangue heaps may also spontaneously combust and cause fires or collapse in the rainy season, causing disasters.
[0020] Fly ash is a resource-based material that can be used as an admixture for cement, mortar, and concrete, and can become a component of these materials. In addition, it can also be used to make building materials such as sintered bricks, autoclaved aerated concrete, foamed concrete, and hollow brickwork. The comprehensive utilization of fly ash can not only reduce environmental pollution, but also save natural resources. However, if fly ash is not treated, it will produce dust to pollute the atmosphere, and if it is discharged into the water system, it will cause river siltation and ecological damage. The activity of fly ash mainly comes from the hydration of active SiO2 (vitreous SiO2) and active Al2O3 (vitreous Al2O3) under certain alkaline conditions. Therefore, active SiO2, active Al2O3 and f-CaO (free calcium oxide) in fly ash are all active and beneficial components.
[0021] Gypsum can be used in cement retarders, gypsum building products, model making, medical food additives, sulfuric acid production, paper fillers, paint fillers, etc. In addition, gypsum is a by-product of the power generation process in power plants with a large output. Its microporous structure and heating dehydration properties make it play an important role in many industries such as construction, medical care and chemical industry.
[0022] The present invention provides a method for preparing a coal gangue mixed solid waste mineralized column, which specifically comprises the following steps: The coal gangue is crushed and mixed with fly ash, gypsum and water to form a slurry, which is stirred and rolled; alkaline substances are added for digestion, and then a prefabricated product is finally formed after injection molding, pressing and curing, that is, a coal gangue mixed solid waste mineralized column. The prefabricated parts can be mass-produced in the factory and then transported to the construction site for assembly, which greatly shortens the construction period. This helps to speed up the progress of the project and reduce the time cost during the construction process. The strength of the prefabricated parts is not less than 38Mpa, preferably 42Mpa.
[0023] The present invention supports the upper overburden layer after assembling the coal gangue mixed solid waste mineralized column. It can also be transported to the coal mining site by a ready-mixed concrete mixer truck, poured into a columnar mold and formed with strength after natural curing to support the upper overburden layer.
[0024] As a raw material, coal gangue needs to be crushed first to reduce its particle size to 2~10mm, preferably 2mm, by jaw crusher, double roll crusher or high pressure roller mill and other equipment. The crushed coal gangue can increase the surface area of the raw material, which is conducive to the subsequent mixing and reaction process. The addition of fly ash and gypsum can improve the physical and mechanical properties and chemical stability of the mixture, and improve the strength, durability and other indicators of the prefabricated products. The addition of water makes the mixture form a slurry with a certain fluidity, which is convenient for subsequent wheel rolling and molding, and forms a slurry after stirring. The stirred slurry is sent to the wheel mill for rolling, and the particles of the slurry are further refined by the action of mechanical force, and made more compact and uniform; it can improve the density and uniformity of the slurry, which is conducive to the formation of a more compact and stable structure in the subsequent molding and curing process, and can reduce the porosity of the mixture, improve its impermeability and durability. Alkaline substances (such as carbide slag, lime and sodium hydroxide, etc.) are added to the slurry after wheel rolling for digestion reaction. Alkaline substances react chemically with the components in the slurry to generate products with gelling properties, which can stimulate the potential hydraulic components in the slurry and form a stable hardened body in the water. Secondly, it can improve the adhesion and strength of the slurry, providing guarantee for the final performance of the prefabricated products. The digested slurry is injected into the mold and pressed. The shape and size of the prefabricated products are selected according to the actual situation to meet the requirements of the engineering design. At the same time, pressing can improve the density and strength of the prefabricated products, ensuring that they can withstand various loads during use. The pressed prefabricated products are placed in a suitable environment for curing. During the curing process, the temperature, humidity and other conditions are controlled to make the moisture in the prefabricated products gradually evaporate, the chemical reaction is fully carried out, and finally a stable hardened body is formed. Curing can improve the strength and durability of the prefabricated products, ensuring that they can maintain stable performance for a long time during use.
[0025] Among them, the alkaline substance is preferably carbide slag; carbide slag is a waste generated in the production process of carbide (calcium carbide), which is rich in alkaline components such as calcium hydroxide. Carbide slag can be mixed with other raw materials such as limestone, clay, etc. in a certain proportion, and made into high-quality cement through processes such as firing. Since carbide slag itself contains a large amount of calcium hydroxide, the amount of lime can be reduced in the cement production process, reducing the production cost. The cement produced using carbide slag has good performance and can meet the needs of construction projects. Since carbide slag and leachate are strongly alkaline and contain toxic and harmful substances such as sulfides and phosphides, if they are directly discharged or piled up without treatment, they will cause serious pollution to the land, air, surface water and groundwater. Secondly, carbide slag is easy to leak and pollute the road surface during transportation. Long-term accumulation not only occupies a large amount of land, but also may cause soil salinization, posing a threat to the ecological environment. The present invention uses carbide slag as an alkaline substance for digestion reaction, which not only reduces production costs, but also realizes the resource utilization of industrial waste.
[0026] Among them, the mass ratio of coal gangue, fly ash, gypsum and alkaline substances is 25:50:15:10; as industrial waste, coal gangue and fly ash are mixed in this ratio to achieve the transformation from waste to useful materials, significantly improve resource utilization and reduce environmental pollution. The high proportion of 50% fly ash reduces the dependence on natural raw materials. At the same time, since the prices of fly ash and coal gangue are usually lower than traditional building materials, it helps to reduce production costs. 15% gypsum helps to adjust the setting time and hardening properties of the mixture and improve the compressive strength and durability of the prefabricated parts. At the same time, the digestion reaction of 10% alkaline substances promotes the release of active components in coal gangue and fly ash, further enhancing the gelling properties of the material. This ratio helps to obtain good workability, such as suitable slump, water seepage rate, etc., making the mixture easy to operate during stirring, wheel rolling, injection molding, etc., reducing material waste and process difficulty.
[0027] The gangue provides a certain strength and skeleton effect, the fly ash improves the fluidity and density of the mixture, the gypsum plays a role in adjusting the setting time and enhancing the strength, and the alkaline substances can effectively stimulate the potential activity in the raw materials such as gangue and fly ash, promote the hydration reaction and hardening process, and improve the strength and durability of the prefabricated products. The synergistic effect of the four makes the prefabricated products have excellent physical and mechanical properties.
[0028] Among them, the mass ratio of the total mass of coal gangue, fly ash and gypsum to water is (3~5):1; the amount of water added is controlled within a reasonable range, avoiding problems such as strength reduction and shrinkage cracks caused by excessive moisture, and ensuring the strength and durability of the prefabricated products.
[0029] The curing process is an autoclave curing process, curing at 180-190°C and 1 MPa for 8-12 hours. The stirring rate is 300-400 rpm. The appropriate stirring rate can ensure that the raw materials such as gangue, fly ash, gypsum and water are fully mixed and uniform during the stirring process to avoid agglomeration and stratification. In actual work, the premixed slurry can also be poured into the columnar mold at the coal mining site, and the column will form strength after 7 days of natural curing.
[0030] In view of the problem that the coal pillar support method causes large coal losses during coal mining and the solid waste generated causes serious environmental pollution, the present invention provides a coal gangue mixed solid waste mineralized pillar that can be replaced with the existing coal pillar. While improving the coal mining rate, coal gangue and fly ash are consumed on a large scale, and waste is controlled throughout the entire process from coal mining to combustion. Through the compounding of solid waste, coal gangue, fly ash and gypsum are mixed and poured into the coal mine to support the overlying rock strata, replacing the original load-bearing coal pillar. At the same time, some of the free calcium oxide components in the fly ash can absorb part of the carbon dioxide in the coal mine, further improving the strength of the pillar.
[0031] The present invention uses fly ash and gypsum instead of cement as cementitious materials, which are mixed with a large amount of coal gangue discarded in the coal mining process to make blocks or premixed concrete, replacing the coal pillars reserved in the coal mining process and playing a supporting role in the coal mine.
[0032] The method for replacing coal pillars with a system of gangue, fly ash and gypsum proposed in the present invention adopts an environmentally friendly concrete formula to replace coal pillars, thereby increasing the mining rate of coal and improving economic benefits. It comprehensively utilizes various wastes in the process of coal mine production and power plant power generation, including gangue, fly ash and gypsum, and reduces environmental pollution.
[0033] Example 1 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 2 mm, and the coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 28 parts of water to form a slurry, which was stirred and wheel-rolled at 300 rpm; 10 parts of calcium carbide slag were added for digestion, and then injection molding and pressing were performed; at 185°C and 1MPa, autoclave curing for 8 hours finally formed a prefabricated product, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240mm×115mm×53mm.
[0034] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive area of the specimen was 27600mm during the compressive strength test. 2First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and align the pressure position with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 42Mpa.
[0035] Example 2 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 4 mm, and the coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 25 parts of water to form a slurry, which was stirred and wheel-rolled at 320 rpm; 10 parts of calcium carbide slag were added for digestion, and then injection molding and pressing were performed; at 180°C and 1.5 MPa, autoclaved and cured for 10 hours to finally form a prefabricated product, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240 mm × 115 mm × 53 mm.
[0036] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 41Mpa.
[0037] Example 3 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 6 mm. The coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 22 parts of water to form a slurry, which was stirred and rolled at 340 rpm. 10 parts of carbide slag were added for digestion, and then injection molded and pressed. After autoclaving and curing at 180°C and 2MPa for 12 hours, a prefabricated product was finally formed, which was a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process was a square mold with an inner diameter of 240mm×115mm×53mm.
[0038] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 44Mpa.
[0039] Example 4 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 8 mm. The coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 20 parts of water to form a slurry, which was stirred and wheel-rolled at 360 rpm. 10 parts of carbide slag were added for digestion, and then injection molding and pressing were performed. After autoclaving and curing at 190°C and 1 MPa for 12 hours, a prefabricated product was finally formed, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240 mm × 115 mm × 53 mm.
[0040] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 47Mpa.
[0041] Example 5 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 10 mm, and the coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 19 parts of water to form a slurry, which was stirred and wheel-rolled at 380 rpm; 10 parts of calcium carbide slag were added for digestion, and then injection molding and pressing were performed; at 190°C and 1.5 MPa, autoclave curing for 10 hours finally formed a prefabricated product, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240 mm × 115 mm × 53 mm.
[0042] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 39Mpa.
[0043] Example 6 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 2 mm. The coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 17 parts of water to form a slurry, which was stirred and rolled at 400 rpm; 10 parts of calcium carbide slag were added for digestion, and then injection molding and pressing were performed; at 190°C and 2MPa, autoclave curing for 8 hours finally formed a prefabricated product, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240mm×115mm×53mm.
[0044] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and align the pressure position with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 42Mpa.
[0045] Example 7 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 2 mm, and the coal gangue particles were mixed with 50 parts of fly ash, 10 parts of gypsum and 17 parts of water to form a slurry, and 10 parts of calcium carbide slag were added. The pre-mixed slurry was poured into a columnar mold at the coal mining site, and after natural curing for 7 days, a coal gangue mixed solid waste mineralization column was formed. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240mm×115mm×53mm.
[0046] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive strength test was carried out on the compressive area of the specimen of 27600mm. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and align the pressure position with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 38Mpa.
[0047] Comparative Example 1 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 2 mm, and the coal gangue particles were mixed with 65 parts of fly ash, 10 parts of gypsum and 28 parts of water to form a slurry, which was stirred and wheel-rolled at 300 rpm; then injection molding and pressing were performed; and after autoclaving and curing at 185°C and 1 MPa for 8 hours, a prefabricated product was finally formed, namely, a coal gangue mixed solid waste mineralization column. Among them, the mold in the injection molding and pressing process is a square mold with an inner diameter of 240 mm × 115 mm × 53 mm.
[0048] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive area of the specimen was 27600mm during the compressive strength test. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 35Mpa.
[0049] Comparative Example 2 25 parts of coal gangue were crushed to form coal gangue particles with a particle size of 2 mm. The coal gangue particles were mixed with 65 parts of fly ash, 10 parts of gypsum and 28 parts of water to form a slurry. The pre-mixed slurry was poured into a columnar mold at the coal mining site. After natural curing for 7 days, a coal gangue mixed solid waste mineralized column was formed.
[0050] The prepared coal gangue mixed solid waste mineralized column was subjected to strength test. The compressive area of the specimen was 27600mm during the compressive strength test. 2 First, remove the debris and particles between the pressure surface of the specimen and the pressure plate, cut the specimen into the main specimen and the auxiliary specimen along the center line, stack them on the test bench for testing, and the pressure position should be aligned with the center of the pressure plate and the bottom plate. The load addition speed is 0.2kN / s until the specimen is destroyed. The test strength is 24Mpa.
[0051] According to the test strength results of Example 1 and Comparative Example 1, adding carbide slag can improve the strength of the coal gangue mixed solid waste mineralized column. Fly ash, gypsum, and carbide slag are used as mineralization synergistic high-temperature alkali-activated active materials to completely replace cement. Fly ash and gypsum have mineralization and hydration activities, participate in mineralization reactions and hydration reactions, and produce a cementitious structure. They are used as active materials for cementitious components. Coal gangue does not participate in the reaction during the curing process, and plays a structural support role as an aggregate.
[0052] According to the test strength results of Example 1 and Comparative Example 2, the strength of the coal gangue mixed solid waste mineralized column obtained after 7 days of natural curing is relatively low. This is because the premixed concrete injection molding method is carried out at the coal mining site, which is sensitive to the humidity and CO2 concentration at the coal mining site. The strength forming is slow, resulting in reduced strength. A certain amount of carbide slag needs to be added to ensure the strength.
[0053] In summary, by adding highly alkaline carbide slag, on the one hand, it ensures the absorption of more CO2 gas, and on the other hand, the reaction releases more heat, ensuring the autoclave curing effect; it effectively delays the solidification of the slurry, ensuring that more gas enters the interior to react with free calcium oxide to form strength.
[0054] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.
Claims
1. A method for preparing a coal gangue mixed solid waste mineralized column, characterized in that: The specific steps include: The coal gangue is crushed and mixed with fly ash, gypsum and water to form a slurry, which is then stirred and rolled; alkaline substances are added to dissolve it, and then a prefabricated product is finally formed after injection molding, pressing and curing, namely, a coal gangue mixed solid waste mineralized column; The mass ratio of the coal gangue, fly ash, gypsum and alkaline substance is 25:50:15:
10.
2. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The alkaline substance is carbide slag.
3. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The mass ratio of the total mass of the coal gangue, fly ash and gypsum to water is (3-5):
1.
4. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The curing process is an autoclave curing process.
5. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 4, characterized in that: The autoclave curing process is curing at 180-190° C. and 1-2 MPa for 8-12 hours.
6. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The strength of the prefabricated part is not less than 38Mpa.
7. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 6, characterized in that: The strength of the prefabricated part is 42Mpa.
8. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The particle size of the coal gangue after crushing is 2-10 mm.
9. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 8, characterized in that: The particle size of the coal gangue after crushing is 2 mm.
10. The method for preparing a coal gangue mixed solid waste mineralized column according to claim 1, characterized in that: The stirring rate is 300-400 rpm.